PENGARUH LINGKUNGAN KERJA DAN INSENTIF TERHADAP PENINGKATAN PRODUKTIVITAS KERJA KARYAWAN Pada PT. J&T Cargo Mahakam Kota Bengkulu - Saputra, Rico Aprilian; Kusuma, Merta (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2023)
This study aims to determine the effect of work environment and incentives on employee productivity at PT. J&T Cargo Mahakam Bengkulu City. The population in this study were all employees at the PT. J&T Cargo Mahakam Bengkulu City. Sampling in this study, using the census method, namely taking the entire existing population. Research data were analyzed using multiple linear regression analysis method. The research results show that (1). The work environment has a positive and significant effect on employee work productivity at PT. J&T Cargo Mahakam Bengkulu City, and (2). Incentives have a positive and significant effect on employee work productivity at PT. J&T Cargo Mahakam Bengkulu City. (3) the work environment and incentives simultaneously influence the work productivity of employees at the PT. J&T Cargo Mahakam Bengkulu City by 75.50%. Key words : Work environment, Incentives and Work Productivity